Induction of gene expression by exon 2 of the major E1A proteins of adenovirus type 5. - Mymryk, J S (1993)
We have constructed an adenovirus type 5 (Ad5) E1A mutant, dl1119/520, that produces essentially only exon 2 of the major E1A proteins. In infected primary baby rat kidney cells, this mutant induced expression of the E1B 55-kDa protein, and in infected human KB cells, it induced expression of this protein, the E2A 72-kDa protein, and hexon. In KB cells, this mutant grew substantially better than Ad5 dl312, which lacks E1A, and as well as Ad5 dl520, an E1A mutant producing only the 243-residue protein. These results suggest that exon 2 of E1A proteins on its own was able to activate gene expression. We also constructed mutants of dl1119/520, containing small deletions in regions of exon 2 that others found to be associated with effects on the properties of E1A transformants. None of these deletions destroyed gene activation completely, indicating that there may be some redundancy among sequences in exon 2 for inducing gene expression. The two deletions that decreased induction the most, residues 224 to 238 and 255 to 270, were in regions reported to be associated with the expression of a metalloprotease and with enhanced transformation, suggesting that exon 2 may regulate expression of genes governing cell growth. It is remarkable that all sections of E1A proteins, exon 1, the unique region, and exon 2, have now been found to affect gene expression.